PENINGKATAN PENDAPATAN KERUPUK CITRA MELALUI PENINGKATAN KUANTITAS DAN KUALITAS PRODUKSI - Yuliastuti, Ida Ayu Nyoman; Lestari, I Gusti Agung Ayu Istri; Purnawati, Ni Luh Gede Putu (Lembaga Penelitian dan Pemberdayaan (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2018)
Cracker or Kerupuk is one of the most popular snack in Indonesia and it can be a business opportunity through a million rupiahs of sales. This opportunity is utilized by Mr. I Putu Soma Antara (40 years old) by setting up a home-made cracker?s business line